The Role of Green Banana in The Dietary Management of Children with Diarrhea: A Systematic Review and Meta Analysis - Ghitha, Nida; Larasati, Anjani; Satari, Heidi; Indira, Fiona Maharani; Devaera, Yoga; Gayatri, Pramita (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Diarrheal disease is a leading cause of morbidity and mortality among children under five, particularly in developing countries. Green bananas have shown therapeutic potential in managing pediatric diarrhea. This systematic review and meta-analysis compared the effectiveness of green banana supplementation versus non-green banana dietary management in children with diarrhea, alongside the use of ORS (oral rehydration solution) and Zinc. Outcomes assessed were recovery days, dehydration status, and progression to persistent diarrhea. Methods: A systematic search was conducted across PubMed, Cochrane, Scopus, and ProQuest databases, following the PRISMA guidelines. Qualitative analysis was assessed using the RoB 2.0. Quantitative analysis was performed using RevMan 5.4 with forest plot visualization. Result: From 57 identified studies, eight were included for review (seven randomized controlled trials and one pilot study). Among 1,486 children receiving green bananas, 1,370 recovered from diarrhea within seven days. Meta analysis showed significantly improved diarrheal recovery with green banana on day 3 (OR 3.41, 95% CI: 2.93-3.98, P<0.00001), day 5 (OR 3.48, 95% CI: 2.15-5.62, P<0.00001), and day 7 (OR 2.86, 95% CI: 2.14-3.82, P<0.00001). Green banana supplementation also showed less frequent dehydration (OR 0.38, 95% CI: 0.16-0.92, P=0.03) and reduced the progression to persistent diarrhea (OR 0.29, 95% CI: 0.21-0.39, P<0.00001). Conclusion: Green banana with high pectin and amylose-resistant starch (ARS), is an effective dietary adjunct in the management of pediatric diarrhea, in terms of improving recovery, reducing dehydration, and preventing prolonged diarrhea in children due to their antimicrobial and anti-inflammatory compounds.